EFFECT OF DIFFERENT PLANT DENSITY ON QUANTITY YIELD OF CHICORY (CICHORIUM INTYBUS L.) IN DIFFERENT WATER CONDITIONS - Farahani, Hossein Aliabadi; Valadabadi, Alireza; Asghari, Mahdi Taheri (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
This experiment was conducted at Iran in 2006. Field experiment was carried out by a split plot design with 4 replications. The factors which studied were according irrigation with 75, 150 and 225 mm water evaporation from evaporation pan and plant density with 6, 9, 12 and 15 plant m-2. The results showed that irrigation according significant effect on biological yield, number of lateral branch, number of leaf, number of pod in main stem, number of pod in plant, number of pod in lateral branch and weight dry matter of leaf and stem (α=1%), root length (α=5%) and root diameter and highest plant were not significantly affected due to water deficit. Means compression showed that highest biological yield, number of lateral branch, highest plant, number of leaf, root length and diameter, number of pod in main stem, number of pod in plant and weight dry matter of leaf and stem were achieved under irrigation according of 75 mm water evaporation. Also plant density significant effect on all chicory characteristics (α=1%) and means compression showed that highest upon characteristics were achieved under 15 plant m-2 and highest root length, number of pod in lateral branch, number of lateral branch, number of pod in main stem, number of leaf and number of pod in plant were achieved under 6 plant m-2. The results this experiment showed that drought stress decreased quantity yield and morphological characteristics of chicory sorely. Key words: chicory, plant density, biological yield and different water conditions.